IMAGE EDGE DETECTION USING ROBINSON OPERATOR - PANDI BARITA NAULI SIMANGSONG (INFOKUM, 2020)
Image processing is now widely used in almost all fields including medicine, industry, agriculture, geology, marine, and so on. One of the main things in image processing is the process of detecting the edge of an image, wherewith this process the boundary edge of an object with its background can be well determined. Edge detection is a method that can be used to detect the edge of an image that aims to improve the appearance of the boundaries of an area or objects in the image so that objects or boundaries of an area in the image are more easily recognized by humans and machines. Edge detection in digital images aims to recognize a pattern contained in the image itself. With the recognition of patterns in an image will be easily obtained information in an image. Determining the location of the edge of an image is easy if the condition of the image is clear and sharp, but the accuracy of the existence of the edge becomes difficult to determine if there is interference in the image, such as noise. But often it also results in an unsustainable image border where the results are influenced by the type of method used.